Style analysis: asset allocation and evaluation of sharia equity fund performance / Opi Prisilia and Acong Dewantoro Marsono. - Prisilia, Opi; Marsono, Acong Dewantoro (Universiti Teknologi MARA Selangor, 2020)
Knowing the funds' style can reduce investment risk. This paper describes the characteristic style of sharia equity funds in Indonesia. We use the return based style analysis model that consists of ten asset class and eight sharia equity funds. The model run by using quadratic program and rolling window method. The results indicate that fund managers apply a passive strategy to manage sharia equity funds. The managers allocate the fund in all asset class proportionally, but they prefer to allocate most of the fund to the trading asset class. Only 12.5% of the sharia equity fund that actual performance outperforms the style performance. The passive strategy style is the best way to manage the sharia equity fund in Indonesia.